2009
DOI: 10.1266/ggs.84.417
|View full text |Cite
|
Sign up to set email alerts
|

A HindIII BAC library construction of Mesobuthus martensii Karsch (Scorpiones:Buthidae): An important genetic resource for comparative genomics and phylogenetic analysis

Abstract: Scorpions are "living but sophisticated fossils" that have changed little in their morphology since their first appearance over the past 450 million years ago. To provide a genetic resource for understanding the evolution of scorpion genome and the relationships between scorpions and other organisms, we first determined the genome size of the scorpion Mesobuthus martensii Karsch (about 600 Mbp) in the order Scorpiones and constructed a HindIII BAC library of the male scorpion M. martensii Karsch from China. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Through the random screening and bioinformatics analysis of the B. martensii venom gland cDNA library described previously [23,25,26,27], we found a new putative α-scorpion toxin BmαTX47 which might act on sodium channels. The precursor nucleotide sequence had 369 bp including a 5' untranslated region (UTR), ORF and 3' UTR of 48 bp, 258 bp and 63 bp, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the random screening and bioinformatics analysis of the B. martensii venom gland cDNA library described previously [23,25,26,27], we found a new putative α-scorpion toxin BmαTX47 which might act on sodium channels. The precursor nucleotide sequence had 369 bp including a 5' untranslated region (UTR), ORF and 3' UTR of 48 bp, 258 bp and 63 bp, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The venom gland cDNA library of the scorpion B. martensii was constructed as described previously [25,44,45]. Random colonies were selected for sequencing using the ABI 3730 automated sequencer.…”
Section: Methodsmentioning
confidence: 99%
“…Karyotype determination has concluded that scorpion chromosomes vary in number and morphology, ranging from a diploid number of <10 up to >100 chromosomes (Schneider et al 2009;Schneider and Cella 2010). Additionally, flow cytometry experiments indicate that the genome size of buthid scorpions might be comprised between 600 (M. martensii, Li et al 2009) and 880 Mbp (Centruroides vittatus, Hanrahan and Johnston 2011).…”
Section: Future Directions For Scorpion Transcriptomicsmentioning
confidence: 99%